2013
DOI: 10.1021/jf304675j
|View full text |Cite
|
Sign up to set email alerts
|

Physiological and Molecular Basis of Acetolactate Synthase-Inhibiting Herbicide Resistance in Barnyardgrass (Echinochloa crus-galli)

Abstract: Barnyardgrass biotypes from Arkansas (AR1 and AR2) and Mississippi (MS1) have evolved cross-resistance to imazamox, imazethapyr, and penoxsulam. Additionally, AR1 and MS1 have evolved cross-resistance to bispyribac-sodium. Studies were conducted to determine if resistance to acetolactate synthase (ALS)-inhibiting herbicides in these biotypes is target-site or non-target-site based. Sequencing and analysis of a 1701 base pair ALS coding sequence revealed Ala₁₂₂ to Val and Ala₁₂₂ to Thr substitutions in AR1 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
99
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 80 publications
(108 citation statements)
references
References 47 publications
(96 reference statements)
7
99
0
2
Order By: Relevance
“…8,16 Samples (3-4 g) of fresh shoot tissue (bulked from 5-8 individual plants) were measured, immediately frozen and ground in liquid nitrogen and stored at −80 ∘ C until further analysis. The herbicide concentrations used were 0, 0.001, 0.01, 0.1, 1, 10, 100 and 1000 M for halosulfuron.…”
Section: Als In Vitro Inhibition Assaymentioning
confidence: 99%
See 1 more Smart Citation
“…8,16 Samples (3-4 g) of fresh shoot tissue (bulked from 5-8 individual plants) were measured, immediately frozen and ground in liquid nitrogen and stored at −80 ∘ C until further analysis. The herbicide concentrations used were 0, 0.001, 0.01, 0.1, 1, 10, 100 and 1000 M for halosulfuron.…”
Section: Als In Vitro Inhibition Assaymentioning
confidence: 99%
“…6,7 Introduction of imidazolinone (IMI)-resistant rice and overreliance on ALS-inhibiting herbicides for several years has led to the evolution of ALS-resistant weeds in midsouthern United States rice. 8 Several reports of ALS-inhibiting herbicide-resistant weeds such as barnyardgrass (Echinochloa crus-galli L.), 9 smallflower umbrella sedge (Cyperus difformis L.) 10 and rice flatsedge (Cyperus iria L.) 11 have been documented in Arkansas rice, which demonstrates considerable adaptive evolution of these weed species to ALS inhibitors. In 2012, a rice grower in Arkansas failed to control yellow nutsedge with halosulfuron.…”
Section: Introductionmentioning
confidence: 99%
“…E. oryzicola cross-resistance to ALSherbicides was due to the result of Trp574Leu mutation. Barnyardgrass biotypes from Arkansas (AR1 and AR2) and Mississippi (MS1) have evolved cross-resistance to ALSinhibiting herbicides, imazamox, imazethapyr, penoxsulam and bispyribac-sodium (Riar et al, 2013). The crossresistance between two or more herbicides in an herbicide resistant weed biotype is conferred by a single mechanism.…”
mentioning
confidence: 99%
“…Riar et al [8] studied three barnyardgrass (Echinochloa crus-galli) biotypes from the United States with cross-resistance to imazamox, imazethapyr, penoxsulam, and bispyribac-sodium. The authors concluded that reduced translocation could contribute to imazamox and bispyribac-sodium resistance for two out of three biotypes.…”
Section: Restriction Of Herbicide Movement In Resistant Weedsmentioning
confidence: 99%